Caffeic Acid Phenethyl Ester and Its Fluorinated Derivative as Natural Anti-obesity Agents (P06-089-19). (13th June 2019) - Rayalam, Srujana; Mills, Devin; Azhar, Yusra; Miller, Ebony; Wang, Xinyu
Abstract: Objectives: Caffeic acid phenethyl ester (CAPE), an active component of propolis from honeybee hives, is well studied for its beneficial effects on cancer, inflammation and diabetes. There are however limited studies investigating the effects of CAPE on obesity. Currently, several natural products are under investigation for their effects on adipocyte life cycle. A multi-targeted approach for prevention and treatment of obesity includes targeting adipocytes at all the stages of life cycle by decreasing adipocyte differentiation, inducing lipolysis and/or by inducing adipocyte apoptosis. In this study, we examined the effects of CAPE on preadipocyte viability, adipogenesis and lipolysis. Earlier reports on CAPE indicate that CAPE is liable to enzymatic hydrolysis in vivo making this compound unstable for therapeutic applications. In the current study, we compared the anti-adipogenic effects of CAPE with its novel fluorinated derivative (FCAPE), a more stable compound. Methods: 3T3-L1 pre-adipocytes were differentiated using a cocktail consisting of insulin, dexamethasone, and isobutyl methyl xanthine in DMEM supplemented with 10% FBS following adipogeneic differentiation. Pre- and mature adipocytes were incubated with CAPE or FCAPE for 24–48 hours and their effects on viability, lipolysis, and adipogenesis was tested using Prestoblue, Lipolysis assay (Zen-Bio) and AdipoRed assay respectively. Results: Our results indicate that neither CAPE nor FCAPE significantly altered preadipocyte viability within the tested dose range. Although both CAPE and FCAPE significantly decreased adipogenesis compared to control, FCAPE decreased lipid content by 73.6 ± 1.6% while CAPE reduced lipid content by only 36.8 ± 9.1% at 25 μM concentration. In contrast to adipogenesis data, our preliminary results with lipolysis assay indicate that only CAPE, but not FCAPE induces lipolysis in mature adipocytes. Conclusions: These findings suggest that both CAPE and FCAPE possess anti-adipogenic properties. Further studies are needed to elucidate their differential effects on adipogenesis and lipolysis. Funding Sources: This study was funded by the Department of Research, PCOM.